Metode Penafsiran Al-Qur’an Menggunakan Pendekatan Linguistik - Arifin Hidayat (Madaniyah, 2017)
Muhammad Syahrur is a doctor in the field of soil mechanics who tries to enter the hermeneutical region of the Book. Through his expertise in engineering combined with linguistic theories, Syahrur succeeded in giving new meaning, as well as criticizing classical religious concepts. The linguistic approach he exposed is inseparable from the influence of some of his teachers, among them Abu Ali al-Farisi, Ibn Jinni, Abdul Qahir al-Jurjani, and so forth. At the applicative level, the method used by Syahrur, in discussing Islam is to acknowledge the existence of Allah s.w.t., to believe in the final day and do good deeds. Anyone who possesses these three traits, is called by Syahrur as a Muslim. The word of faith in the Qur'an according to Syahrur has the meaning of polivaen. Faith in some verses is defined by Islam, and in others it has the meaning of "believing in Prophet Muhammad s.a.w.".